Infrared Interlayer Exciton Emission in MoS2/WSe2 Heterostructures - Karni, Ouri; Barré, Elyse; Lau, Sze Cheung; Gillen, Roland; Ma, Eric Yue; Kim, Bumho; Watanabe, Kenji; Taniguchi, Takashi; Maultzsch, Janina; Barmak, Katayun; Page, Ralph H.; Heinz, Tony F. (Physical Review Letters, 2019)
We report light emission around 1 eV (1240 nm) from heterostructures of MoS2 and WSe2 transition metal dichalcogenide monolayers. We identify its origin in an interlayer exciton (ILX) by its wide spectral tunability under an out-of-plane electric field. From the static dipole moment of the state, its temperature and twist-angle dependence, and comparison with electronic structure calculations, we assign this ILX to the fundamental interlayer transition between the K valleys in this system. Our findings gain access to the interlayer physics of the intrinsically incommensurate MoS2/WSe2 heterostructure, including moiré and valley pseudospin effects, and its integration with silicon photonics and optical fiber communication systems operating at wavelengths longer than 1150 nm.
CRIS-Team Scopus Importer:2019-12-27